Extracts of pomelo peels prevent high-fat diet-induced metabolic disorders in c57bl/6 mice through activating the PPARα and GLUT4 pathway. - Xiaobo Ding (PLoS ONE, 2013)
OBJECTIVE:Metabolic syndrome is a serious health problem in both developed and developing countries. The present study investigated the anti-metabolic disorder effects of different pomelo varieties on obese C57BL/6 mice induced by high-fat (HF) diet. DESIGN:The peels of four pomelo varieties were extracted with ethanol and the total phenols and flavonoids content of these extracts were measured. For the animal experiment, the female C57BL/6 mice were fed with a Chow diet or a HF diet alone or supplemented with 1% (w/w) different pomelo peel extracts for 8 weeks. Body weight and food intake were measured every other day. At the end of the treatment, the fasting blood glucose, glucose tolerance and insulin (INS) tolerance test, serum lipid profile and insulin levels, and liver lipid contents were analyzed. The gene expression analysis was performed with a quantitative real-time PCR assay. RESULT:The present study showed that the Citrus grandis liangpinyou (LP) and beibeiyou (BB) extracts were more potent in anti-metabolic disorder effects than the duanshiyou (DS) and wubuyou (WB) extracts. Both LP and BB extracts blocked the body weight gain, lowered fasting blood glucose, serum TC, liver lipid levels, and improved glucose tolerance and insulin resistance, and lowered serum insulin levels in HF diet-fed mice. Compared with the HF group, LP and BB peel extracts increased the mRNA expression of PPARα and its target genes, such as FAS, PGC-1α and PGC-1β, and GLUT4 in the liver and white adipocyte tissue (WAT). CONCLUSION:We found that that pomelo peel extracts could prevent high-fat diet-induced metabolic disorders in C57BL/6 mice through the activation of the PPARα and GLUT4 signaling. Our results indicate that pomelo peels could be used as a dietary therapy and the potential source of drug for metabolic disorders.